Precision Higgs Constraints in U(1) Extensions of the Standard Model with a Light Z′-Boson - Zoltán Péli; Zoltán Trócsányi (Universe)
Anomaly-free <semantics>U(1)</semantics> extensions of the standard model (SM) predict a new neutral gauge boson <semantics>Z′</semantics>. When <semantics>Z′</semantics> obtains its mass from the spontaneous breaking of the new <semantics>U(1)</semantics> symmetry by a new complex scalar field, the model also predicts a second real scalar s, and the search for the new scalar and the search for the new gauge boson become intertwined. We present the computation of production cross sections and decay widths of such a scalar s in models with a light <semantics>Z′</semantics> boson when the decay <semantics>h→Z′Z′</semantics> may have a sizeable branching ratio. We show how the Higgs signal strength measurement in this channel can provide stricter exclusion bounds on the parameters of the model than those obtained from the total signal strength for Higgs boson production.